Do market-based networks reflect true exposures between banks? - Ben R. Craig; Madina Karamysheva; Dilyara Salakhova (European Central Bank (ECB), 2023)
We compare networks constructed using five commonly used methods and publicly available daily market data to networks based on reported exposures along several dimensions of the balance sheet, i.e., loans, bonds, equity. Our findings suggest that while the global network structure remains stable, individual exposures are more dynamic. The main message from the regression analysis is that the market-based networks do their job relatively well, however, various market-based networks capture different types of exposures. All the measures reflect common portfolios of bonds and loans. Equity-based measures match better direct and indirect equity, while credit-risk measures capture direct bonds. None of the measures robustly identify direct interbank lending.
Keywords: G20; L14; D85; C63; 330; banking regulation; financial networks; interconnections; market-based networks; true-exposure networks